Promoting diversity tolerance among Indonesians through smart mobile civic media in Citizenship Education - Trisiana, Anita; Triyanto, Triyanto; Zakaria, Gamal Abdul Nasir; Sakinah, Sakinah; Arvinth, N (Universitas Negeri Yogyakarta, 2025)
The formation of student characters is carried out with variations in the form of digital-based